Nature the Ultimate Inspiration for Art: Its Capabilities and Role to Conserve and Sustain the Environment: Exploring the Connection Between Art and Nature (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Art and nature has always been correlated and connected since beginning of human existence and history of art. Art took inspiration from nature and civilization and art and culture developed along with environment with the resources it offered. Early example of nature’s impact can be found in cave paintings presenting aspects of nature through drawing of animals, human figures and symbolic drawings by observing nature. Art evolved with human civilization by utilizing its resources like metal and stone to create both utilitarian and non utilitarian works and connected art with way of living. With evolution of human artistic creativity and stability art explored its boundaries with natural surroundings. Art flourished in form of monumental sculptures, murals, paintings and became a part of civilizations that existed. With the spread of industrialization and modern development of urban cities the environment suffered and became imbalanced. The population explosion created pressure on nature’s natural resources and contaminated them on a larger scale. The dramatic habitat destruction, contamination of air water and land and drastic depletion of forests impacted the ecosystem and its balance in nature. This created the need for art that is environmental and sustainable in nature. The site specific land art emerged as a movement and artists started creating works in collaboration with physical world. Public art came up with new definition of public welfare rather than just publically accessible outdoor art. Artists saw the need to think of art which does not disrupt the environment but sync with natural surroundings and inspire for coexistence with nature. Natural mediums were encouraged and waste or scraps were incorporated to collaborate with natural spaces. Minimum disruption of environment during art expression led to a change in art scenario in the world through evolving trend of ecological land art. In urban and public spaces outdoor art created a great platform to inspire and engage larger audiences about ecological awareness of the nature. This wave of eco friendly sustainable expression of art is enhancing our relationship with nature and inspiring human race to give back the nature what we consumed and conserve its treasure. Art as a way of living surrounds us and impact us with understanding of emotions and self awareness. Art through music literature sculptures installations etc uplifts our spirit and inspire us to improve in every aspect of life. Being an impactful medium of expression art plays a major role for needed change in the society. Nature being basic inspiration for art and foundation of living world need to be given back by using art medium to spread awareness sensitivity and hope toward our natural habitat.